Benedictine Abbey in Senieji Trakai – Specifics of Functioning - Pietrzkiewicz, Iwona (History / Istorija, 2025)
The Benedictine Abbey in Senieji Trakai is one of the oldest monastic foundations in the Grand Duchy of Lithuania, established as early as the beginning of the 15th century. For hundreds of years it has preserved the characteristics typical of St Benedict’s spirituality (contemplative life, asceticism, officium divinum), but had to adapt to local requirements. The most important issue was the running of the parish. Hence the development of pastoral ministry, preaching, the widespread administration of the sacraments, the promotion of devotion to the Virgin Mary and the running of the Confraternity of the Holy Scapular. Despite periodic difficulties, it maintained an adequate spiritual and intellectual level, but also fostered religious culture and had an educational role in the immediate environment.